Pengaruh Model Pembelajaran PBL Berbantuan Chatgpt Terhadap Kreativitas Dan Hasil Belajar Siswa Pada Mata Pelajaran Informatika - Vivi Revinasari (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
This research looks to see how using the Problem Based Learning (PBL) method with help from ChatGPT impacts the creativity and learning success of Grade VIII students in the Informatics class at SMP Negeri 30 Tebo. The study used numbers and an experimental style with a design called Intact Group Comparison. There were 84 students in the entire eighth grade, and the researchers chose 46 students to form two groups: one was the experimental group, and the other was the control group. To gather data, they used a creativity survey and a test to measure learning progress, both of which were checked to ensure they were accurate and reliable. The data was analyzed through tests for normality, homogeneity, and an independent sample t-test. The findings from the study showed that using the PBL method with ChatGPT significantly improved students’ creativity and learning results. This was supported by the t-test results that indicated a significance level below 0.05. PBL method with ChatGPT is a good way to enhance students’ creativity and their performance in Informatics.